2022
DOI: 10.5171/2022.203744
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable e-Health System Development in COVID 19 Pandemic – The Theoretical Studies of Knowledge Management Systems and Practical Polish Healthcare Experience

Abstract: The paper describes the sustainable e-health system concerning the theoretical studies and practical Polish healthcare experience. The aim of the paper is to describe the theoretical issues of sustainable development in e-health, and to show practical issues of information and communication technologies (ICTs) as the knowledge management factor in healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Thus, many organizations within the healthcare settings are fine-tuning their HIS to be resilient and sustainable. However, the realization of a robust information system within the healthcare arena is challenging and depends on the flow of information as a crucial constituent for suave and efficient functioning [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, many organizations within the healthcare settings are fine-tuning their HIS to be resilient and sustainable. However, the realization of a robust information system within the healthcare arena is challenging and depends on the flow of information as a crucial constituent for suave and efficient functioning [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the healthcare industry, there is a high demand for knowledge to enhance healthcare applications [ 49 , 62 ]. Several studies reported that the deployment of knowledge management in the healthcare arena is set to enhance healthcare treatment effectiveness [ 49 , 58 , 61 ]. Many stakeholders such as governments, World Health Organization (WHO), and healthcare workers rely on the management of healthcare knowledge to complement healthcare applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Piorunkiewicz and Morawiec [16] have published a study detailing the significance of AI in long-term e-health systems from a theoretical perspective in light of the practical Polish healthcare experience. However, this research was limited in that it did not specifically address security and privacy concerns, as well as design and integration challenges; instead, it merely described the conceptual problems of sustainable growth in e-health and made some suggestions about the role of ICT as a knowledge management factor in the healthcare system.…”
Section: Existing Workmentioning
confidence: 99%